หิกมะฮฺของการมีภรรยาหลายคนตามหลักกฎหมายอิสลาม และการนำไปใช้ของครอบครัวมุสลิมในจังหวัดนราธิวาส: The Wisdom of Polygamy in Islamic law and Application of the Muslim family In Narathiwat Province. - สามะ, นูรีฮะ; แตอาลี, อัสมัน (Al-HIKMAH Journal, 2019)
The objectives of this study were 1) to study the principles and wisdoms of polygamy in Islamic laws, 2) to study the applications of polygamy of the Muslims family in Islamic Laws in Narathiwat province. This research was a qualitative research by using document research and in-depth Interview, colleted Muslims family having polygamy 5 families in Narathiwat Province. The results found that: Islam provide a complete way of life and cover in all their dimension. The rulings on permits plural marrige is a righteous following to the nature of man life. Its also creat balanced the number of women in a society that the number of woman is greater than the number of men in age. The applications in creating the islamic way of the muslims family including polygamy in Narathiwat province have several issue, such as 1.Justice or Fairness 2.The ability to spend on one' wives 3.To give household 4. Equally in spending the night with them 5.Taking care of his family The almost successful to apply the polygamy of muslims family caused by person in the family to have deep understandings in principles, rulings, wisdoms of polygamy. That is to say, Muslims family have more the knowledge and understanding can apply it than muslims family have few the understanding as low to lowest.